Covering blanket for concrete curing in winter and preparation method thereof

By using a covering blanket containing an endothermic insulation layer in winter concrete curing, the cracks caused by temperature differences are solved, effective insulation and moisturizing effects are achieved, and the service life of the concrete is extended.

CN119593600APending Publication Date: 2025-03-11QINGDAO BAOTIAN CONSTR ENG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411758184.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

After pouring concrete in winter, temperature differences caused by internal hydration reactions can easily lead to cracks on the surface of the concrete structure, affecting its strength and service life. In the prior art, sponge blankets lack heat production effects, while electric heating blankets have energy consumption and safety hazards.

Method used

A covered blanket for winter concrete curing is used, including a moisturizing layer, an adhesive layer, a sponge layer, an adhesive layer and an endothermic insulation layer. The heat-absorbing insulation layer consists of polyether polyols, isocyanates, breathable particles, foaming agents, carbon black and nitrogen-doped graphene. The foaming effect of the foaming agent forms porous polyurethane, and combines the heat-absorbing effect of carbon black and nitrogen-doped graphene to improve the heat-absorbing and insulation properties of the covering blanket.

Benefits of technology

The covering blanket absorbs solar energy through the heat-absorbing insulation layer during the day in winter, and maintains a higher temperature when the temperature is low at night. Combined with the insulation effect of the sponge layer, it effectively reduces the impact of external low temperature on the concrete surface, reduces the generation of cracks, and extends the service life of concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005166873070000101
    Figure BDA0005166873070000101
  • Figure BDA0005166873070000111
    Figure BDA0005166873070000111
Patent Text Reader

Abstract

The invention relates to the field of concrete curing, and particularly discloses a covering blanket for concrete curing in winter and a preparation method thereof.The covering blanket for concrete curing in winter comprises a moisturizing layer, a bonding layer, a sponge layer, a bonding layer and a heat absorption and heat preservation layer; the heat absorption and insulation layer comprises 80-100 parts of polyether polyol, 80-100 parts of isocyanate, 5-10 parts of breathable particles, 10-20 parts of a foaming agent, 20-40 parts of carbon black, 10-20 parts of nitrogen-doped graphene, 1-3 parts of a dispersing agent and 10-20 parts of a chain extender; the preparation method comprises the following steps: spraying a bonding liquid on the surface of the moisturizing layer, then adhering the sponge layer to the bonding liquid, and drying; the surface of the other side of the sponge layer is sprayed with bonding liquid, then the heat absorption and heat preservation layer is bonded, and the covering blanket is obtained after drying; the concrete has the advantages of heat preservation and moisture preservation effects, capability of controlling the difference between the internal temperature of the concrete and the winter environment temperature, difficulty in cracking of the concrete during winter maintenance and capability of ensuring the strength of the concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of concrete curing, and more specifically, to a covering blanket for winter concrete curing and a preparation method thereof. Background Art

[0002] After concrete is poured, the internal temperature of the concrete will rise sharply due to the hydration reaction. After pouring concrete in winter, due to the large temperature difference between the internal hydration temperature of the concrete and the external ambient temperature, cracks may easily appear on the surface of the concrete structure, affecting the strength and service life of the concrete.

[0003] Traditional concrete maintenance generally uses sponge blankets or electric heating blankets for covering. Although sponge blankets have good thermal insulation effects and can block the low temperature outside, they do not produce heat themselves. In the winter in the Northeast, the outside temperature is as low as -20°C and the hydration temperature can reach up to 60°C, resulting in a huge temperature difference between the inside and outside of the concrete. Therefore, electric heating blankets are gradually being widely used. However, electric heating blankets not only consume energy, but also electric heating is prone to short circuits. If a short circuit occurs, it is easy to cause a fire, and the safety factor is low.

[0004] Therefore, how to prepare a new covering blanket that has heat preservation and moisture retention effects during winter concrete curing, and can control the temperature difference between the internal temperature of the concrete and the winter ambient temperature, so that the concrete is not prone to cracks during winter curing and ensure the strength of the concrete, is a problem to be solved. Summary of the invention

[0005] In order to prepare a new covering blanket, which has the effect of heat preservation and moisture retention during the winter concrete curing process, and can control the temperature difference between the internal temperature of the concrete and the winter ambient temperature, so that the concrete is not prone to cracks during winter curing and the strength of the concrete is guaranteed, the present application provides a covering blanket for winter concrete curing and a preparation method thereof.

[0006] In the first aspect, the present application provides a covering blanket for winter concrete maintenance, which adopts the following technical solution: A covering blanket for winter concrete maintenance, the covering blanket comprising a moisture retaining layer, a bonding layer, a sponge layer, a bonding layer, and a heat absorbing and heat-insulating layer; The heat-absorbing and heat-insulating layer comprises the following raw materials in parts by weight: 80-100 parts of polyether polyol, 80-100 parts of isocyanate, 5-10 parts of breathable particles, 10-20 parts of foaming agent, 20-40 parts of carbon black, 10-20 parts of nitrogen-doped graphene, 1-3 parts of dispersant, and 10-20 parts of chain extender.

[0007] By adopting the above technical solution, the moisture retaining layer is the inner layer, in contact with the concrete surface, and the heat absorbing and thermal insulation layer is the outermost layer, which can receive solar energy. The covering blanket absorbs heat during the day in winter, and when the temperature is lower at night, the temperature of the heat absorbing and thermal insulation layer is higher than the ambient temperature. Combined with the thermal insulation effect of the heat absorbing and thermal insulation layer and the sponge layer, the influence of the low temperature external environment in winter on the surface temperature of the concrete is reduced, so that the concrete is not prone to cracks during the winter maintenance process, thereby ensuring the strength of the concrete.

[0008] By utilizing the better moisturizing effect of the moisturizing layer, after contacting with the concrete surface, the moisture of the concrete is maintained to achieve the effect of moisturizing and curing the concrete in winter; by utilizing the thermal insulation effect of the sponge layer, the interior of the concrete is isolated from the external environment, and the temperature released by the hydration of the concrete is not easy to lose quickly. At the same time, by utilizing the heat absorption effect of the heat-absorbing thermal insulation layer, it can absorb solar energy to generate heat, further increasing the temperature of the covering blanket, ensuring the curing effect of the concrete in winter, and making it less likely for the concrete to crack during the winter curing process, thereby ensuring the strength of the concrete.

[0009] The polyether polyol, isocyanate and foaming agent are matched, and the foaming effect of the foaming agent is utilized to prepare a porous polyurethane to form a heat-absorbing and heat-insulating layer. The filling and air-permeable effects of the breathable particles are matched to further improve the porosity, and the higher the porosity, the better the heat-insulating effect. The heat-absorbing effect of carbon black and nitrogen-doped graphene is matched, wherein the introduction of nitrogen atoms in the nitrogen-doped graphene increases the Fermi level of the graphene, increases the carrier concentration, and improves the interlayer barrier effect of the two-dimensional layered structure of the nitrogen-doped graphene, thereby facilitating the storage of more heat while reducing heat loss, improving the heat-absorbing effect while ensuring the heat-insulating effect, and the nitrogen-doped graphene can also improve the interface connection effect between the graphene and the polyurethane material, ensuring the structural stability and the heat-absorbing and heat-insulating effect. The heat-insulating effect of the polyurethane foaming layer is matched, and in the winter concrete curing process, it can achieve the effects of heat absorption and heat preservation, thereby making it difficult for the concrete to have surface cracks, thereby ensuring the strength and service life of the concrete.

[0010] Preferably, the nitrogen-doped graphene is prepared by the following method: The graphene oxide is immersed and dispersed in a citric acid solution at a mass ratio of 1:8-10, and then the graphene oxide is filtered out, and then immersed and dispersed in a urea solution and an ethylenediamine solution, and the mass ratio of the graphene oxide to the urea solution and the ethylenediamine solution is 1:15-25:5-15; then calcined and annealed to obtain a semi-finished product, and post-treated to obtain nitrogen-doped graphene.

[0011] By adopting the above technical scheme, graphene oxide utilizes its better adsorption effect to adsorb citric acid. The acidity of the citric acid solution is utilized to not only further ensure the porosity of the graphene oxide, but also can provide a carbon skeleton as a carbon source material. The carbon atoms of the carbon skeleton can combine with nitrogen atoms. In combination with urea solution and ethylenediamine solution, the carboxyl groups in citric acid are easy to attract hydroxyl groups in urea and amino groups in ethylenediamine, further promoting the formation of nitrogen-doped structure on the surface of nitrogen-doped graphene, so that the layered nitrogen-doped graphene tends to a spherical structure after doping. The nitrogen-doped graphene tending to a spherical structure has higher heat absorption and thermal insulation effects, thereby improving the heat absorption and thermal insulation effects of the covering blanket, ensuring that cracking problems are not easy to occur during winter concrete maintenance, thereby ensuring the strength and service life of the concrete.

[0012] Preferably, the post-processing steps are as follows: The semi-finished product is uniformly dispersed in a polyethylene glycol solution at a mass ratio of 1:1-3, and then granulated by spray drying.

[0013] By adopting the above technical scheme, the semi-finished product is treated with a polyethylene glycol solution and then spray-dried, so that the semi-finished product is further made to tend to a spherical structure, and the surface of the nitrogen-doped graphene is made rich in hydroxyl groups. The hydroxyl groups of the polyethylene glycol on the surface of the nitrogen-doped graphene can be matched with polyether polyols and isocyanates to improve the cross-linking effect of the nitrogen-doped graphene and the polyurethane, thereby improving the adhesion stability of the nitrogen-doped graphene in the polyurethane foaming layer. Combined with the heat absorption and thermal insulation effects of the nitrogen-doped graphene and the thermal insulation effect of the polyurethane foaming layer, the cold air in winter can be further blocked from affecting the hydration of the concrete surface, the generation of cracks on the concrete surface can be reduced, and the strength of the concrete can be ensured.

[0014] Preferably, the carbon black is prepared by treating carbon black particles with glycerol citrate.

[0015] By adopting the above technical scheme, carbon black particles and glyceryl citrate are matched, and the glyceryl citrate on the surface of carbon black uses its carboxyl group to facilitate connection with substances such as polyether polyols and isocyanates, while the ester group has a certain hydrophobic effect, so that the heat-absorbing and thermal insulation layer has a certain hydrophobic effect after absorbing the heat of solar energy, and can partially block the low-temperature water mist in the external environment.

[0016] Preferably, the breathable particles are composed of pectin-coated silica aerogel and polycaprolactone diol-modified expanded graphite in a mass ratio of 1:1-2.

[0017] By adopting the above technical scheme, pectin-coated silica aerogel and polycaprolactone diol-modified expanded graphite are matched, and the pectin on the surface of the silica aerogel is combined with the polycaprolactone diol on the surface of the expanded graphite to improve the cross-linking effect of the pectin-coated silica aerogel, the polycaprolactone diol-modified expanded graphite with polyether polyol and isocyanate; pectin has a certain barrier effect, which can block the polyether polyol from blocking the pores of the silica aerogel and ensure the porosity of the breathable particles; the expanded graphite also has a porous structure, and the polycaprolactone diol has a hydrophobic effect, which blocks the pores of the expanded graphite from being blocked by substances such as polyether polyol, and the higher porosity of the expanded graphite and the silica aerogel is used to improve the thermal insulation effect of the heat-absorbing and thermal insulation layer, thereby improving the thermal insulation effect of the covering blanket.

[0018] The combination of pectin-coated silica aerogel and polycaprolactone diol-modified expanded graphite can have a certain moisturizing effect by utilizing the hygroscopic effect of pectin, while polycaprolactone diol has a hydrophobic effect, which can block the low-temperature moisture in the external environment from affecting the temperature of the heat-absorbing and thermal-insulating layer; combined with the heat-absorbing effect of expanded graphite, the heat-absorbing and thermal-insulating layer has both good heat-absorbing effect and good thermal insulation and moisture retention, which protects the concrete from cracks after winter curing, thereby ensuring the strength of the concrete.

[0019] Preferably, the pectin-coated silica aerogel is made of silica aerogel, hydrogen peroxide solution and high-fat pectin solution in a mass ratio of 1:0.3-0.5:0.5-1.

[0020] By adopting the above technical scheme, the silica aerogel, the hydrogen peroxide solution and the high-fat pectin solution are matched, and the adsorption effect of the silica aerogel is used to facilitate the adsorption of the hydrogen peroxide solution, and then the high-fat pectin solution is used for surface coating. As the hydrogen peroxide solution is thermally decomposed to release gas, the air permeability of the high-fat pectin solution after film formation is further guaranteed, and the porosity of the silica aerogel is guaranteed, which is not easily blocked by materials such as polyether polyols, thereby ensuring that the heat-absorbing and thermal-insulating layer has a good thermal-insulating effect; the hydroxyl group of the high-fat pectin on the surface of the silica aerogel is easy to connect with the polyether polyol and isocyanate, so that the pectin-coated silica aerogel is tightly connected with the polyurethane, thereby ensuring the heat-absorbing and thermal-insulating effect of the heat-absorbing and thermal-insulating layer.

[0021] Preferably, the polycaprolactone diol-modified expanded graphite is made of expanded graphite and polycaprolactone diol in a mass ratio of 1:0.2-0.5.

[0022] By adopting the above technical scheme, polycaprolactone diol is adsorbed by expanded graphite, and the hydroxyl group in polycaprolactone diol is used to facilitate connection with polyether polyol and isocyanate, thereby improving the connection effect between polycaprolactone diol-modified expanded graphite and polyurethane; combined with the hydrophobic effect of polycaprolactone diol, it is not easy for the modified expanded graphite to absorb moisture from the external environment, and polycaprolactone diol can improve the toughness and low-temperature characteristics of the heat-absorbing and thermal-insulating layer. Under the lower temperature in winter, the heat-absorbing and thermal-insulating layer is not easily damaged, so that the concrete has a better covering effect during the curing process, concrete cracks are not easy to appear, and the life of the concrete is extended.

[0023] Preferably, the moisturizing layer comprises the following raw materials in parts by weight: 80-100 parts of sodium carboxymethyl cellulose solution, 1-5 parts of chitosan fiber, 2-5 parts of sepiolite fiber, 1-5 parts of aluminum silicate fiber, 5-10 parts of carbon fiber, and 1-5 parts of boron nitride particles.

[0024] By adopting the above technical scheme, the sodium carboxymethyl cellulose solution has a good bonding effect, and can tightly bond the chitosan fiber, sepiolite fiber, aluminum silicate fiber, carbon fiber and boron nitride particles; the high porosity of the chitosan fiber, sepiolite fiber, aluminum silicate fiber and boron nitride particles is utilized to give the moisturizing layer a good thermal insulation effect; the high porosity of the chitosan fiber, sepiolite fiber, aluminum silicate fiber and boron nitride particles, combined with their good adsorption effect and the hydrophilic effect of the carboxymethyl cellulose, makes the moisturizing layer have a good moisturizing effect, ensures that the concrete surface is well moisturized, and is not prone to the problem of concrete cracks during the winter concrete maintenance process, thereby ensuring the strength of the concrete; combined with the good thermal conductivity of carbon fiber, thermal conductivity is ensured, and the solar heat absorbed by the heat-absorbing and heat-insulating layer during the day can be partially insulated in the moisturizing layer, reducing the temperature difference between the concrete surface and the interior of the concrete, further preventing cracks from occurring on the concrete surface during the winter concrete maintenance process, thereby ensuring the strength of the concrete and extending the service life of the concrete.

[0025] Preferably, the bonding layer is made of a bonding liquid, and the bonding liquid is made of a polyvinyl alcohol solution and carbon fibers in a mass ratio of 1:0.1-0.2.

[0026] By adopting the above technical scheme, polyvinyl alcohol solution and carbon fiber are matched, and the good bonding effect of polyvinyl alcohol solution is utilized to facilitate bonding of the moisture retaining layer, the sponge layer, and the heat absorbing and insulating layer, thereby improving the structural stability of the covering blanket, and making the covering blanket have the effect of heat preservation and moisture retention at the same time. During the winter concrete curing process, it can reduce the cracks on the concrete surface, thereby ensuring the strength of the concrete.

[0027] In a second aspect, the present application provides a method for preparing a covering blanket for winter concrete maintenance, which adopts the following technical solution: A method for preparing a covering blanket for winter concrete maintenance comprises the following steps: S1. Spray the adhesive liquid evenly on the surface of the moisturizing layer, and then adhere the sponge layer to the adhesive liquid. After drying, the adhesive liquid becomes an adhesive layer; S2. Spray the bonding liquid evenly on the surface of the other side of the sponge layer, and then bond the heat-absorbing and heat-insulating layer. After drying, the bonding liquid becomes a bonding layer to obtain a finished covering blanket.

[0028] By adopting the above technical solution, the prepared covering blanket has a heat preservation and moisture retention effect during the winter concrete curing process, and can control the temperature difference between the internal temperature of the concrete and the winter ambient temperature, so that the concrete is not prone to cracks during winter curing, thereby ensuring the strength of the concrete.

[0029] In summary, this application has the following beneficial effects: 1. The moisture retaining layer is the inner layer, in contact with the concrete surface, while the heat absorbing and thermal insulation layer is the outermost layer, which can receive solar energy. The covering blanket absorbs heat during the day in winter, and when the temperature is lower at night, the temperature of the heat absorbing and thermal insulation layer is higher than the ambient temperature. Combined with the thermal insulation effect of the heat absorbing and thermal insulation layer and the sponge layer, the influence of the low temperature external environment in winter on the surface temperature of the concrete is reduced, making it less likely for the concrete to crack during the winter maintenance process, thereby ensuring the strength of the concrete.

[0030] 2. Polyether polyol, isocyanate and foaming agent are matched, and the foaming effect of the foaming agent is utilized to prepare a porous polyurethane to form a heat-absorbing and thermal-insulating layer, which is combined with the heat-absorbing effect of carbon black and nitrogen-doped graphene. The introduction of nitrogen atoms in nitrogen-doped graphene increases the Fermi level of graphene, increases the carrier concentration, and improves the interlayer barrier effect of the two-dimensional layered structure of nitrogen-doped graphene, thereby facilitating the storage of more heat while reducing heat loss, improving the heat absorption effect while ensuring the thermal insulation effect. Nitrogen-doped graphene can also improve the interface connection effect between graphene and polyurethane materials, ensure structural stability and heat-absorbing and thermal-insulating effects; make concrete less likely to have surface cracks, and ensure the strength and service life of concrete. DETAILED DESCRIPTION

[0031] The present application is further described in detail below with reference to the embodiments.

[0032] Preparation example of nitrogen-doped graphene Among the following raw materials, graphene oxide was purchased from Jiangxi Shuobang New Material Technology Co., Ltd.; other raw materials are all commercially available.

[0033] Preparation Example 1: Nitrogen-doped graphene is prepared by the following method: 1 kg of graphene oxide is placed in 9 kg of citric acid solution, immersed and stirred for 10 minutes at 1000 r / min, the average particle size of the graphene oxide is 40 μm, and the citric acid solution is a citric acid aqueous solution with a mass fraction of 5%; then the graphene oxide is filtered out, and then placed in 20 kg of urea solution and 10 kg of ethylenediamine solution, the urea solution is a urea aqueous solution with a mass fraction of 10%, and the ethylenediamine solution is an ethylenediamine aqueous solution with a mass fraction of 10%, stirred for 10 minutes at a speed of 1000 r / min, and mixed evenly; in an argon atmosphere, the temperature is increased to 400° C. at a heating rate of 5° C. / min, allowed to stand for 30 minutes, and then continued to be heated to 900° C. for calcination, kept warm for 1 hour, and annealed to obtain a semi-finished product; 1 kg of the semi-finished product is uniformly dispersed in 2 kg of polyethylene glycol solution, the polyethylene glycol solution is a polyethylene glycol aqueous solution with a mass fraction of 2%, and the polyethylene glycol is polyethylene glycol 800, and then spray-dried and granulated to obtain nitrogen-doped graphene.

[0034] Preparation Example 2: This preparation example differs from Preparation Example 1 in that: 1 kg of graphene oxide is placed in 8 kg of citric acid solution, immersed and stirred for 10 minutes at 1000 r / min, the average particle size of the graphene oxide is 40 μm, and the citric acid solution is a citric acid aqueous solution with a mass fraction of 5%; then the graphene oxide is filtered out, and then placed in 15 kg of urea solution and 15 kg of ethylenediamine solution, the urea solution is a urea aqueous solution with a mass fraction of 10%, and the ethylenediamine solution is an ethylenediamine aqueous solution with a mass fraction of 10%, stirred for 10 minutes at a speed of 1000 r / min, and mixed evenly; in an argon atmosphere, the temperature is increased to 400° C. at a heating rate of 5° C. / min, allowed to stand for 30 minutes, and then continued to increase the temperature to 900° C. for calcination, kept warm for 1 hour, and annealed to obtain a semi-finished product; 1 kg of the semi-finished product is uniformly dispersed in 1 kg of polyethylene glycol solution, the polyethylene glycol solution is a polyethylene glycol aqueous solution with a mass fraction of 2%, and the polyethylene glycol is polyethylene glycol 800, and then spray-dried to obtain nitrogen-doped graphene.

[0035] Preparation Example 3: This preparation example differs from Preparation Example 1 in that: 1 kg of graphene oxide is placed in 10 kg of citric acid solution, immersed and stirred for 10 minutes at 1000 r / min, the average particle size of the graphene oxide is 40 μm, and the citric acid solution is a citric acid aqueous solution with a mass fraction of 5%; then the graphene oxide is filtered out, and then placed in 25 kg of urea solution and 5 kg of ethylenediamine solution, the urea solution is a urea aqueous solution with a mass fraction of 10%, and the ethylenediamine solution is an ethylenediamine aqueous solution with a mass fraction of 10%, stirred for 10 minutes at a speed of 1000 r / min, and mixed evenly; in an argon atmosphere, the temperature is increased to 400° C. at a heating rate of 5° C. / min, allowed to stand for 30 minutes, and then continued to increase the temperature to 900° C. for calcination, kept warm for 1 hour, and annealed to obtain a semi-finished product; 1 kg of the semi-finished product is uniformly dispersed in 3 kg of polyethylene glycol solution, the polyethylene glycol solution is a polyethylene glycol aqueous solution with a mass fraction of 2%, and the polyethylene glycol is polyethylene glycol 800, and then spray-dried to obtain nitrogen-doped graphene.

[0036] Preparation Example of Carbon Black The citrate glyceride in the following raw materials was purchased from Wuhan Shuer Biotechnology Co., Ltd., CAS: 32691-32-4, liquid, content 99%; other raw materials are all commercially available.

[0037] Preparation Example 4: Carbon black was prepared by the following method: 1 kg of carbon black particles were placed in 3 kg of citric acid glyceride, and the mixture was stirred under pressure at a pressure of 0.5 MPa and a rotation speed of 1000 r / min for 10 minutes, and then the carbon black particles were separated to obtain carbon black; the average particle size of the carbon black particles was 60 μm, and the average porosity was 45%.

[0038] Example of Preparation of Pectin Coated Silica Aerogel The following raw materials are all commonly available on the market.

[0039] Preparation Example 5: Pectin-coated silica aerogel was prepared by the following method: 0.4 kg of hydrogen peroxide solution is added to 1 kg of silica aerogel, and the addition rate of the hydrogen peroxide solution is 120 g / min. During the addition process, the silica aerogel is stirred at a rotation speed of 200 r / min, and then 0.8 kg of high-fat pectin solution is evenly sprayed on the surface of the silica aerogel, dried at 100° C. for 20 minutes, and then dispersed until the silica aerogels are not adhered to each other and agglomerated, so as to obtain a finished product; the average particle size of the silica aerogel is 20 μm, and the average porosity is 90%; the concentration of the hydrogen peroxide solution is 5%; 1 kg of high-fat pectin and 3 kg of white sugar are mixed and stirred evenly, and hot water at 85° C. is added, and stirred until the solute is completely dissolved, so as to obtain a high-fat pectin solution with a concentration of 3%.

[0040] Preparation Example 6: This preparation example differs from Preparation Example 5 in that: 0.3 kg of hydrogen peroxide solution was added to 1 kg of silica aerogel at a rate of 120 g / min. During the addition, the silica aerogel was stirred at a speed of 200 r / min. Then, 0.5 kg of high-fat pectin solution was evenly sprayed on the surface of the silica aerogel, dried at 100° C. for 20 min, and then dispersed until the silica aerogels did not stick to each other and agglomerate to obtain a finished product.

[0041] Preparation Example 7: This preparation example differs from Preparation Example 5 in that: 0.5 kg of hydrogen peroxide solution was added to 1 kg of silica aerogel at a rate of 120 g / min. During the addition, the silica aerogel was stirred at a speed of 200 r / min. Then, 1 kg of high-fat pectin solution was evenly sprayed on the surface of the silica aerogel, dried at 100° C. for 20 minutes, and then dispersed until the silica aerogels did not stick to each other and agglomerated to obtain a finished product.

[0042] Preparation example of polycaprolactone diol modified expanded graphite The polycaprolactone diol in the following raw materials was purchased from Hubei Yamade Biopharmaceutical Co., Ltd.; other raw materials were commercially available.

[0043] Preparation Example 8: Polycaprolactone diol-modified expanded graphite is prepared by the following method: 0.4 kg of polycaprolactone diol was added to 1 kg of expanded graphite, the average particle size of the expanded graphite was 40 μm, the average porosity was 85%, the adding speed was 120 r / min, the stirring speed of the expanded graphite during the adding process was 200 r / min, the mixture was mixed and stirred evenly, and the polycaprolactone diol-modified expanded graphite was obtained.

[0044] Preparation Example 9: This preparation example differs from Preparation Example 8 in that: 0.2 kg of polycaprolactone diol was added to 1 kg of expanded graphite at a speed of 120 r / min. During the adding process, the expanded graphite was stirred at a speed of 200 r / min. The mixture was mixed and stirred evenly to obtain polycaprolactone diol-modified expanded graphite.

[0045] Preparation Example 10: This preparation example differs from Preparation Example 8 in that: 0.5 kg of polycaprolactone diol was added to 1 kg of expanded graphite at a speed of 120 r / min. During the adding process, the expanded graphite was stirred at a speed of 200 r / min. The mixture was mixed and stirred evenly to obtain polycaprolactone diol-modified expanded graphite.

[0046] Preparation example of heat absorbing and insulating layer The polyether polyol and isocyanate in the following raw materials were purchased from Shandong Huibang New Material Technology Co., Ltd., and the isocyanate was isocyanate PM200; Preparation Example 11: The heat-absorbing and heat-insulating layer is prepared by the following method: 90 kg of polyether polyol, 90 kg of isocyanate, and 15 kg of chain extender were weighed and mixed evenly, and then 8 kg of breathable particles, 30 kg of carbon black, 15 kg of nitrogen-doped graphene, and 2 kg of dispersant were added and mixed evenly, and finally 15 kg of foaming agent was added and mixed evenly, and foamed at 90 ° C for 2 hours. After cutting, a heat-absorbing and thermal-insulating layer was obtained, and the average thickness of the heat-absorbing and thermal-insulating layer was 3 mm; the chain extender was ethylene glycol; the breathable particles were composed of pectin-coated silica aerogel prepared in Preparation Example 5 and polycaprolactone diol-modified expanded graphite prepared in Preparation Example 8 in a mass ratio of 1:1; the carbon black was selected from the carbon black prepared in Preparation Example 4; the nitrogen-doped graphene was selected from the nitrogen-doped graphene prepared in Preparation Example 1; the dispersant was propylene glycol.

[0047] Preparation Example 12: This preparation example differs from Preparation Example 11 in that: 80 kg of polyether polyol, 80 kg of isocyanate, and 10 kg of chain extender were weighed and mixed evenly, and then 5 kg of breathable particles, 20 kg of carbon black, 10 kg of nitrogen-doped graphene, and 1 kg of dispersant were added and mixed evenly, and finally 10 kg of foaming agent was added and mixed evenly, and foamed at 90 ° C for 2 hours, and cut to obtain a heat-absorbing and thermal insulation layer; the breathable particles are composed of pectin-coated silica aerogel prepared in Preparation Example 6 and polycaprolactone diol-modified expanded graphite prepared in Preparation Example 9 in a mass ratio of 1:1; the carbon black is the carbon black prepared in Preparation Example 4; the nitrogen-doped graphene is the nitrogen-doped graphene prepared in Preparation Example 2.

[0048] Preparation Example 13: This preparation example differs from Preparation Example 11 in that: 100 kg of polyether polyol, 100 kg of isocyanate, and 20 kg of chain extender were weighed and mixed evenly, then 10 kg of breathable particles, 40 kg of carbon black, 20 kg of nitrogen-doped graphene, and 3 kg of dispersant were added and mixed evenly, and finally 20 kg of foaming agent was added and mixed evenly, and foamed at 90 ° C for 2 hours, and cut to obtain a heat-absorbing and thermal insulation layer; the breathable particles are composed of pectin-coated silica aerogel prepared in Preparation Example 7 and polycaprolactone diol-modified expanded graphite prepared in Preparation Example 10 in a mass ratio of 1:2; the carbon black is the carbon black prepared in Preparation Example 4; the nitrogen-doped graphene is the nitrogen-doped graphene prepared in Preparation Example 3.

[0049] Example of preparing a moisturizing layer The following raw materials are all commercially available.

[0050] Preparation Example 14: The moisturizing layer is prepared by the following method: Weigh 90kg of sodium carboxymethyl cellulose solution, 3kg of chitosan fiber, 4kg of sepiolite fiber, 4kg of aluminum silicate fiber, 8kg of carbon fiber and 3kg of boron nitride particles, mix and stir evenly, and obtain a moisturizing layer by casting and drying; the average thickness of the moisturizing layer is 2mm; the sodium carboxymethyl cellulose solution is a sodium carboxymethyl cellulose aqueous solution with a mass fraction of 1%, the average length of the chitosan fiber is 500μm, the average length of the sepiolite fiber is 500μm, the average length of the aluminum silicate fiber is 500μm, the average length of the carbon fiber is 200μm, and the average particle size of the boron nitride particles is 40μm.

[0051] Preparation Example 15: This preparation example differs from Preparation Example 14 in that: Weigh 80 kg of sodium carboxymethyl cellulose solution, 1 kg of chitosan fiber, 2 kg of sepiolite fiber, 1 kg of aluminum silicate fiber, 5 kg of carbon fiber and 1 kg of boron nitride particles, mix and stir evenly, and obtain a moisturizing layer by casting and drying.

[0052] Preparation Example 16: This preparation example differs from Preparation Example 14 in that: Weigh 100 kg of sodium carboxymethyl cellulose solution, 5 kg of chitosan fiber, 5 kg of sepiolite fiber, 5 kg of aluminum silicate fiber, 10 kg of carbon fiber and 5 kg of boron nitride particles, mix and stir evenly, and obtain a moisturizing layer by casting and drying. Example

[0053] Embodiment 1: A covering blanket for winter concrete maintenance: S1. Spray the adhesive liquid evenly on the surface of the moisturizing layer, and then adhere the sponge layer to the surface of the adhesive liquid. After drying, the adhesive liquid forms an adhesive layer. The average thickness of the sponge layer is 3 mm, and the average thickness of the adhesive layer is 100 μm. Add 0.15 kg of carbon fiber to 1 kg of polyvinyl alcohol solution and mix and stir evenly to obtain an adhesive liquid. Select the heat-absorbing and heat-insulating layer prepared in Preparation 11 and the moisturizing layer prepared in Preparation Example 14; S2. Spray the bonding liquid evenly on the surface of the sponge layer away from the moisturizing layer, adhere the heat absorbing and thermal insulation layer to the bonding liquid surface, and after drying, the bonding liquid forms a bonding layer with an average thickness of 100 μm to obtain a finished covering blanket; the covering blanket is composed of five layers, namely, a moisturizing layer, a bonding layer, a sponge layer, a bonding layer, and a heat absorbing and thermal insulation layer.

[0054] Embodiment 2: This embodiment differs from Embodiment 1 in that: S1. Spray the adhesive liquid evenly on the surface of the moisturizing layer, and then adhere the sponge layer to the surface of the adhesive liquid. After drying, the adhesive liquid forms an adhesive layer. The average thickness of the sponge layer is 3 mm, and the average thickness of the adhesive layer is 100 μm. Add 0.1 kg of carbon fiber to 1 kg of polyvinyl alcohol solution and mix and stir evenly to obtain an adhesive liquid. Select the heat-absorbing and thermal-insulating layer prepared in Preparation 12 and the moisturizing layer prepared in Preparation Example 15.

[0055] Embodiment 3: This embodiment differs from Embodiment 1 in that: S1. Spray the adhesive liquid evenly on the surface of the moisturizing layer, and then adhere the sponge layer to the surface of the adhesive liquid. After drying, the adhesive liquid forms an adhesive layer. The average thickness of the sponge layer is 3 mm, and the average thickness of the adhesive layer is 100 μm. Add 0.2 kg of carbon fiber to 1 kg of polyvinyl alcohol solution and mix and stir evenly to obtain an adhesive liquid. Select the heat-absorbing and thermal-insulating layer prepared in Preparation 13 and the moisturizing layer prepared in Preparation Example 16.

[0056] Embodiment 4: This embodiment differs from Embodiment 1 in that: No citric acid solution was added during the preparation of nitrogen-doped graphene.

[0057] Embodiment 5: This embodiment differs from Embodiment 1 in that: No post-treatment was performed during the preparation of nitrogen-doped graphite; Specifically, 1 kg of graphene oxide is placed in 9 kg of citric acid solution, immersed and stirred for 10 minutes at 1000 r / min, the average particle size of the graphene oxide is 40 μm, and the citric acid solution is a citric acid aqueous solution with a mass fraction of 5%; then the graphene oxide is filtered out, and then placed in 20 kg of urea solution and 10 kg of ethylenediamine solution, the urea solution is a urea aqueous solution with a mass fraction of 10%, and the ethylenediamine solution is a 10% ethylenediamine aqueous solution with a mass fraction, stirred at a speed of 1000 r / min for 10 minutes, and mixed evenly; in an argon atmosphere, the temperature is increased to 400°C at a heating rate of 5°C / min, allowed to stand for 30 minutes, and then continued to be heated to 900°C for calcination, kept warm for 1 hour, and annealed to obtain nitrogen-doped graphene.

[0058] Embodiment 6: This embodiment differs from Embodiment 1 in that: The air permeable particles in the heat-absorbing and heat-insulating layer are replaced by the same mass of silica aerogel to replace the pectin-coated silica aerogel, and the same mass of expanded graphite to replace the polycaprolactone diol-modified expanded graphite.

[0059] Embodiment 7: This embodiment differs from Embodiment 1 in that: The air permeable particles in the heat-absorbing and heat-insulating layer are replaced by polycaprolactone-modified expanded graphite of the same mass as polycaprolactone-modified expanded graphite, that is, polycaprolactone replaces polycaprolactone-diol.

[0060] Embodiment 8: This embodiment differs from Embodiment 1 in that: No carbon fiber and boron nitride particles are added to the moisturizing layer; no carbon fiber is added to the adhesive liquid.

[0061] Comparative Example Comparative Example 1: The difference between this comparative example and Example 1 is that: No breathable particles are added to the raw materials of the heat-absorbing and thermal-insulating layer.

[0062] Comparative Example 2: The difference between this comparative example and Example 1 is that: No carbon black and nitrogen-doped graphene are added to the raw materials of the heat-absorbing and thermal-insulating layer.

[0063] Performance testing 1. Crack detection The methods of Examples 1-8 and Comparative Examples 1-2 were respectively used to maintain concrete constructed in winter. The outdoor ambient temperature after concrete pouring was -10°C, the relative humidity was 55%, and the sun was irradiated for 8 hours during the day. A covering blanket was covered on the concrete surface for maintenance. After 7 days of maintenance, the number of cracks on the concrete surface per unit area and the total cracked area were calculated and the data were recorded.

[0064] 2. Temperature difference detection The methods of Examples 1-8 and Comparative Examples 1-2 were respectively used to maintain concrete constructed in winter. The outdoor ambient temperature after concrete pouring was -10°C, and the sun was irradiated for 8 hours during the day. A covering blanket was covered on the concrete surface for maintenance. After maintenance for 24 hours, the temperature of the contact surface between the covering blanket and the concrete surface was detected and recorded as the covering maintenance surface temperature. The temperature difference = covering maintenance surface temperature - outdoor temperature was recorded. The data was recorded. The larger the temperature difference, the better the thermal insulation effect, and the smaller the temperature difference, the worse the thermal insulation effect of the covering blanket.

[0065] The concrete for the above-mentioned test items is poured large-volume concrete. During the test of each group of items, except for the different covering blanket samples in the embodiments or comparative examples, other conditions are the same, following the single variable principle.

[0066] Table 1 Performance test table In combination with Examples 1-3 and Table 1, it can be seen that the covering blanket prepared in the present application has fewer cracks, smaller cracking area, and larger temperature difference during winter concrete curing, indicating that the covering blanket can moisturize and heat the concrete surface, ensuring that the concrete is not prone to cracking during the curing process, and blocking the external low temperature, further ensuring that the concrete is not prone to cracking.

[0067] It can be seen from Example 1 and Examples 4-8 and Table 1 that no citric acid solution was added during the preparation of nitrogen-doped graphene in Example 4. Compared with Example 1, the number of cracks in Example 4 is greater than that in Example 1, the cracking area is greater than that in Example 1, and the temperature difference is less than that in Example 1; this indicates that adding citric acid solution to prepare nitrogen-doped graphene can make the layered nitrogen-doped graphene tend to a spherical structure, improve the heat absorption and thermal insulation effects, and thus reduce the number of cracks.

[0068] No post-treatment was performed during the preparation of the nitrogen-doped graphite in Example 5. Compared with Example 1, the number of cracks in Example 5 was greater than that in Example 1, the cracking area was greater than that in Example 1, and the temperature difference was less than that in Example 1. This indicates that polyethylene glycol on the surface of nitrogen-doped graphene can improve the connection effect between nitrogen-doped graphene and polyether polyol and isocyanate, thereby improving the structural density and ensuring the maintenance effect of concrete in winter.

[0069] In Example 6, the air permeable particles in the heat-absorbing and heat-insulating layer are replaced with pectin-coated silica aerogels with the same mass of silica aerogels, and the polycaprolactone diol-modified expanded graphite is replaced with the same mass of expanded graphite. Compared with Example 1, Example 6 has more cracks than Example 1, a larger crack area, and a smaller temperature difference than Example 1; this illustrates the cross-linking effect of pectin-coated silica aerogels, polycaprolactone diol-modified expanded graphite, polyether polyols, and isocyanates, and utilizes the pores of silica aerogels, and The porous structure of expanded graphite improves the thermal insulation effect of the covering blanket. Polycaprolactone diol has a hydrophobic effect, which prevents the pores of expanded graphite from being blocked by substances such as polyether polyols. The higher porosity of expanded graphite and silica aerogel is utilized to improve the thermal insulation effect of the heat-absorbing and thermal-insulating layer, thereby improving the thermal insulation effect of the covering blanket. Combined with the heat-absorbing effect of expanded graphite, the heat-absorbing and thermal-insulating layer has both good heat-absorbing effect and good thermal insulation and moisture retention, which protects the concrete from cracks after winter curing, thereby ensuring the strength of the concrete.

[0070] In Example 7, the air permeable particles in the heat absorption and thermal insulation layer are replaced by polycaprolactone-modified expanded graphite of equal mass instead of polycaprolactone diol-modified expanded graphite, that is, polycaprolactone replaces polycaprolactone diol. Compared with Example 1, Example 7 has more cracks than Example 1, a larger crack area, and a smaller temperature difference than Example 1. This indicates that polycaprolactone does not have hydroxyl groups, which can easily affect the connection effect of expanded graphite with polyether polyols and isocyanates, thereby affecting the uniformity of heat absorption and thermal insulation of the covering blanket. Polycaprolactone diol-modified expanded graphite can make the covering blanket have better thermal insulation and moisturizing effects, thereby preventing the generation of cracks on the concrete surface.

[0071] In Example 8, no carbon fiber and boron nitride particles were added to the moisturizing layer; no carbon fiber was added to the adhesive liquid. Compared with Example 1, the number of cracks in Example 8 was greater than that in Example 1, the cracking area was greater than that in Example 1, and the temperature difference was less than that in Example 1; this indicates that carbon fiber, carbon fiber and boron nitride particles all have good heat absorption and thermal insulation effects, can improve the heat absorption and thermal insulation effects of the covering blanket, reduce the occurrence of cracks during winter concrete maintenance, and ensure the strength of the concrete.

[0072] Combining Example 1 and Comparative Examples 1-2 and Table 1, it can be seen that no breathable particles are added to the raw materials of the heat-absorbing and thermal-insulating layer of Comparative Example 1. Compared with Example 1, the number of cracks in Comparative Example 1 is greater than that in Example 1, the cracking area is greater than that in Example 1, and the temperature difference is less than that in Example 1; this indicates that the addition of breathable particles can increase the porosity, thereby improving the thermal insulation effect of the covering blanket and reducing the crack problem of concrete.

[0073] In Comparative Example 2, no carbon black and nitrogen-doped graphene are added to the raw materials of the heat-absorbing and thermal-insulating layer. Compared with Example 1, the number of cracks in Comparative Example 2 is greater than that in Example 1, the cracking area is greater than that in Example 1, and the temperature difference is less than that in Example 1; this indicates that the combination of carbon black and nitrogen-doped graphene can improve the thermal insulation and heat absorption effects of the covering blanket, thereby protecting the maintenance effect of concrete in winter and making the concrete less prone to cracks.

[0074] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A covering blanket for winter concrete maintenance, characterized in that: The covering blanket comprises a moisture-retaining layer, an adhesive layer, a sponge layer, an adhesive layer, and a heat-absorbing and heat-insulating layer; The heat-absorbing and heat-insulating layer comprises the following raw materials in parts by weight: 80-100 parts of polyether polyol, 80-100 parts of isocyanate, 5-10 parts of breathable particles, 10-20 parts of foaming agent, 20-40 parts of carbon black, 10-20 parts of nitrogen-doped graphene, 1-3 parts of dispersant, and 10-20 parts of chain extender.

2. The covering blanket for winter concrete maintenance according to claim 1, characterized in that: The nitrogen-doped graphene is prepared by the following method: The graphene oxide is immersed and dispersed in a citric acid solution at a mass ratio of 1:8-10, and then the graphene oxide is filtered out, and then immersed and dispersed in a urea solution and an ethylenediamine solution, and the mass ratio of the graphene oxide to the urea solution and the ethylenediamine solution is 1:15-25:5-15; then calcined and annealed to obtain a semi-finished product, and post-treated to obtain nitrogen-doped graphene.

3. A covering blanket for winter concrete maintenance according to claim 2, characterized in that: The specific steps of the post-processing are as follows: The semi-finished product is uniformly dispersed in a polyethylene glycol solution at a mass ratio of 1:1-3, and then granulated by spray drying.

4. A covering blanket for winter concrete maintenance according to claim 1, characterized in that: The carbon black is prepared by treating carbon black particles with citric acid glyceride.

5. The covering blanket for winter concrete maintenance according to claim 1, characterized in that: The air-permeable particles are composed of pectin-coated silica aerogel and polycaprolactone diol-modified expanded graphite in a mass ratio of 1:1-2.

6. A covering blanket for winter concrete maintenance according to claim 5, characterized in that: The pectin-coated silica aerogel is prepared from silica aerogel, hydrogen peroxide solution and high-fat pectin solution in a mass ratio of 1:0.3-0.5:0.5-1.

7. A covering blanket for winter concrete maintenance according to claim 5, characterized in that: The polycaprolactone diol modified expanded graphite is made of expanded graphite and polycaprolactone diol in a mass ratio of 1:0.2-0.

5.

8. The covering blanket for winter concrete maintenance according to claim 1, characterized in that: The moisturizing layer comprises the following raw materials in parts by weight: 80-100 parts of sodium carboxymethyl cellulose solution, 1-5 parts of chitosan fiber, 2-5 parts of sepiolite fiber, 1-5 parts of aluminum silicate fiber, 5-10 parts of carbon fiber, and 1-5 parts of boron nitride particles.

9. The covering blanket for winter concrete maintenance according to claim 1, characterized in that: The bonding layer is made of a bonding liquid, and the bonding liquid is made of a polyvinyl alcohol solution and carbon fibers in a mass ratio of 1:0.1-0.

2.

10. The method for preparing a covering blanket for winter concrete curing according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Spray the adhesive liquid evenly on the surface of the moisturizing layer, and then adhere the sponge layer to the adhesive liquid. After drying, the adhesive liquid becomes an adhesive layer; S2. Spray the bonding liquid evenly on the surface of the other side of the sponge layer, and then bond the heat-absorbing and heat-insulating layer. After drying, the bonding liquid becomes a bonding layer to obtain a finished covering blanket.